2017
DOI: 10.1080/0284186x.2017.1420909
|View full text |Cite
|
Sign up to set email alerts
|

Pre-existing diabetes mellitus and all-cause mortality in cancer patients: a register-based study in Latvia

Abstract: Interestingly, we found better overall survival of diabetic men during the first years after cancer diagnosis. We hypothesize that access to health services may be advantageous to diabetic patients who are in close contact with the healthcare system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 21 publications
1
10
1
Order By: Relevance
“…Some types of cancer are treated less aggressively in cancer survivors with diabetes than those without diabetes (18). In our study, prediagnosis diabetes increased the risk of all-cause mortality after adjusting for covariables in breast and prostate cancer sites, which is not consistent with previous findings (19,20). But additional evidence indicated that pre-existing diabetes increased the risk of all-cause mortality among women with breast cancer after adjusting for covariables related to delayed diagnosis and therapy (21).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Some types of cancer are treated less aggressively in cancer survivors with diabetes than those without diabetes (18). In our study, prediagnosis diabetes increased the risk of all-cause mortality after adjusting for covariables in breast and prostate cancer sites, which is not consistent with previous findings (19,20). But additional evidence indicated that pre-existing diabetes increased the risk of all-cause mortality among women with breast cancer after adjusting for covariables related to delayed diagnosis and therapy (21).…”
Section: Discussioncontrasting
confidence: 99%
“…But additional evidence indicated that pre-existing diabetes increased the risk of all-cause mortality among women with breast cancer after adjusting for covariables related to delayed diagnosis and therapy (21). In addition, pre-diagnosis diabetes increased the risk of allcause mortality in colorectal cancer survivors in our study, which is consistent with findings in previous study (20).…”
Section: Discussionsupporting
confidence: 92%
“…One study [ 32 ] only presented a Kaplan Meier curve, from which the number of deaths were estimated and used to calculate a risk estimate and 95% CI using the indirect log hazard ratio and variance estimation method from Parmer et al [ 33 ]. If studies presented results separately by endometrial cancer histology type (two studies [ 34 , 35 ]), race (two studies [ 19 , 21 ]) or follow-up time (one study [ 36 ]) these estimates were combined using a fixed effects model to produce one estimate before entering into the meta-analysis model[ 37 ]. As there was an overlap between the populations in two studies assessing endometrial cancer-specific survival, separate results were taken according to race; the Olson et al [ 21 ] study was restricted to black endometrial cancer patients whilst the Lam et al [ 38 ] study was restricted to white endometrial cancer patients, and treated separately.…”
Section: Discussionmentioning
confidence: 99%
“…As there was an overlap between the populations in two studies assessing endometrial cancer-specific survival, separate results were taken according to race; the Olson et al [ 21 ] study was restricted to black endometrial cancer patients whilst the Lam et al [ 38 ] study was restricted to white endometrial cancer patients, and treated separately. Additionally, one study [ 36 ] reported outcomes for endometrial cancer patients identified by two methods (cancer registry and National Health Service) and to avoid potential overlap in patients, only the risk estimate from patients identified from the cancer registry were included in the meta-analysis as this is deemed to be a higher quality source for cancer case identification [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The present study identified twelve national clinical diabetes registries spread over four different continents, mostly concentrated in the Northern part of Europe [13,14,57,[65][66][67][68][69][70][71][72]. Altogether, these databases comprised a total of 7,181,356 diabetic patients.…”
Section: Discussionmentioning
confidence: 99%